2013
DOI: 10.1080/08098131.2013.809783
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of live versus recorded lullabies in preterm infants

Abstract: The aim of this study was to compare the effects of live and recorded lullabies on physiological and behavioural state outcomes of stable preterm infants. We conducted a prospective, repeated measures crossover study, involving 35 stable infants of less than 32 weeks postmenstrual age. Each infant received a different intervention for three consecutive days (live lullabies, recorded lullabies, and no-music sessions). The infant was observed every 5 min for 30 min before, 20 min during, and 30 min after the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 37 publications
3
59
0
8
Order By: Relevance
“…These results support the findings of previous studies that showed the benefits of live music on the physiological and behavioral responses of the preterm infant (Arnon et al, 2006;Ettenberger et al, 2014;Garunkstiene et al, 2014;Loewy et al, 2013). In particular, live music interventions with infant-contingent singing promoted the infant's self-regulation and development (Haslbeck, 2014;Malloch et al, 2012;Shoemark, 2011).…”
Section: Disc Discus Ussion Sionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results support the findings of previous studies that showed the benefits of live music on the physiological and behavioral responses of the preterm infant (Arnon et al, 2006;Ettenberger et al, 2014;Garunkstiene et al, 2014;Loewy et al, 2013). In particular, live music interventions with infant-contingent singing promoted the infant's self-regulation and development (Haslbeck, 2014;Malloch et al, 2012;Shoemark, 2011).…”
Section: Disc Discus Ussion Sionsupporting
confidence: 82%
“…Research showed greater benefits of music therapy with live music (Arnon et al, 2006;Garunkstiene, Buinauskiene, Uloziene, & Markuniene, 2014) and emphasized the importance of the parent's inclusion and accompaniment (Ettenberger et al 2014;Edwards, 2011;Haslbeck, 2014). Nevertheless, most research focuses on the effects of recorded music on the preterm infant, without investigating maternal perspectives and mother-infant interaction (Haslbeck, 2012).…”
Section: Intr Introduction Oductionmentioning
confidence: 99%
“…For example, some interventions were limited to 1 day for 1 to 1.5 h, others to 45 s twice per day over a course of 2 to 6 weeks, and still others ranged from 15 to 45 min over a course of 1 to 6 days. 30,41,49,51,65–67,69,70,87,9096,100,103,104,108 It remains unclear what the potential is for improving outcomes if such sensory exposures occurred consistently throughout NICU hospitalization. Moreover, evidence related to vestibular, kinesthetic and olfactory/gustatory interventions is not as well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Music interventions have improved infant's vital signs, increased levels of quiet alert or quiet sleep states (Loewy, Stewart, Dassler, Telsey, & Homel, 2013), improved weight gain and reduced length of hospitalisation compared to a control group (Garunkstiene, Buinauskiene, Uloziene, & Markuniene, 2014;Saliba, Esseily, Filippa, Kuhn, & Gratier, 2017;Standley, 2012;van Der Heijden et al, 2016). The long-term effects have so far been insufficiently studied (Bieleninik et al, 2016;Haslbeck, 2012).…”
mentioning
confidence: 99%